2010
DOI: 10.1007/s00540-009-0841-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in a patient with undetectable tracheal narrowing on chest radiography

Abstract: We report here a 59-year-old man with a saber-sheath tracheal narrowing who was scheduled to undergo pharyngeal tumor resection under general anesthesia. The tracheal narrowing was not clearly detected by chest radiography during the preoperative examination, but it was visible on axial computed tomography (CT) images taken earlier for diagnostic purposes. Following fiber optic examination of the narrowed segment with the patient under anesthesia, the tube was inserted into the trachea using an Airway Scope. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Safe airway management is a predisposition for every surgery requiring endotracheal intubation. Any kind of malformation of the trachea can be challenging for an anesthesiologist, especially if unrecognized before entering the operating room [9]. Standard preoperative imaging, if not required differently, generally includes only a chest X-ray, but tracheal malformations may not always be apparent, as in this case.…”
Section: Discussionmentioning
confidence: 98%
“…Safe airway management is a predisposition for every surgery requiring endotracheal intubation. Any kind of malformation of the trachea can be challenging for an anesthesiologist, especially if unrecognized before entering the operating room [9]. Standard preoperative imaging, if not required differently, generally includes only a chest X-ray, but tracheal malformations may not always be apparent, as in this case.…”
Section: Discussionmentioning
confidence: 98%
“…As an alternative way of airway evaluation, video laryngoscopy has a broader view, but may induce a more potent stimulus than fibroscopy. During active bleeding of supraglottic tumor, video laryngoscopy is suggested ( 15 ). On severe pharyngeal edema while difficult tracheal intubation was anticipated, it was reported that intubation through an air-Q intubating laryngeal airway successfully secured ventilation with preserved spontaneous breathing ( 16 ).…”
Section: Discussionmentioning
confidence: 99%